Do ecosystem insecurity and social vulnerability lead to failure of water security? - Scott, C.A., Zilio, M.I., Harmon, T., Zuniga-Teran, A., Díaz-Caravantes, R., Hoyos, N., Perillo, G.M.E., Meza, F., Varady, R.G., Neto, A.R., Velez, M.I., Martín, F., Escobar, J., Piccolo, M.C., Mussetta, P., Montenegro, S., Rusak, J.A., Pineda, N. (My University, 2021)
Achieving water security for humans and ecosystems is a pervasive challenge globally. Extensive areas of the Americas are at significant risk of water insecurity, resulting from global-change processes coupled with regional and local impacts. Drought, flooding, and water quality challenges pose significant threats, while at the same time, rapid urban expansion, competing water demands, river modifications, and expanding global markets for water-intensive agricultural products drive water insecurity. This paper takes a social-ecological systems perspective, aiming to identify examples and pathways towards resilient ecosystems and social development. It draws on lessons from two science-policy network projects, one focusing on water scarcity in arid and semi-arid regions of Argentina, Chile, Brazil, Peru, Mexico and the United States and the second addressing river and lake basins as sentinels of climate variability and human effects on water quantity and quality in Canada, the United States, Argentina, Colombia, Uruguay and Chile. Together, these &lsquocomplementary contrasts&rsquo provide an analytical basis to empirically examine stakeholder engagement, knowledge co-production and science-policy interaction supporting decision-making to achieve water security. The paper identifies four tenets for decision-making based on water-security-focused global-change science in the Americas: 1) Decision makers should focus on protecting ecosystems because water security (along with food and energy security) depend on them 2) Water-use and allocation decisions ought to be made considering future environmental and societal vulnerabilities, especially climate projections 3) Holistic approaches (at basin or other appropriate levels) are best suited to ensure social-ecological system resilience and reduce vulnerability and 4) It is essential to support local/traditional livelihoods, and underserved populations to achieve equitable water security and ecosystem resilience.
Keywords: River basins; Water security; Social vulnerability; Decision-making; Ecosystem resilience